Mengungkap Potensi Kecerdasan Buatan untuk Usaha Mikro, Kecil, dan Menengah: Systematic Literature Review - Muhammad Raihan Satrio Putra Pamungkas; Angellina Asyivadibrata; Tasya Susilawati; Mochamad Nurul Huda (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Artificial intelligence has undergone rapid evolution, reaching a level of sophistication where it is now considered a personal assistant, aiding humans in their daily tasks. The potential of artificial intelligence can be observed in almost every sector of life including the business sector. Limited resources and skill capabilities especially for micro, small, and medium enterprises tend to hinder progress. However, given the current advanced level of artificial intelligence, it has emerged as an innovative and cost-effective solution to support business actors. This research systematically examines and discusses the potential of utilizing artificial intelligence in the business sector from credible and scientific sources. A systematic literature review methodology is used for this study. The review encompasses Scopus-indexed journals published between 2019 and 2023, with additional open-access publications. Based on the research findings, 106 studies were found, however, after the screening process the number of studies is reduced to 13 articles. Customer churn management emerged as the most prominent utilization of artificial intelligence. On the other hand, from a technological perspective, optimization technique emerged as the most frequently addressed topic in the examined studies.